2015
DOI: 10.1111/cmi.12536
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages mediate flagellin induced inflammasome activation and host defense in zebrafish

Abstract: Summary The inflammasome is an innate immune complex whose rapid inflammatory outputs play a critical role in controlling infection, however the host cells that mediate inflammasome responses in vivo are not well defined. Using zebrafish larvae, we examined the cellular immune responses to inflammasome activation during infection. We compared the host responses to two Listeria monocytogenes strains: wild type and Lm-pyro, a strain engineered to activate the inflammasome via ectopic expression of flagellin. Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
79
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 74 publications
3
79
0
Order By: Relevance
“…Similar early innate immune cell infiltrates consisting of predominantly macrophages were observed in zebrafish infected with inflammasome-activating L. monocytogenes ultimately resulting in attenuation (Fig. 7.2) (Vincent et al 2015). Previous work with Salmonella enterica subsp Typhimurium similarly engineered to robustly activate the inflammasome suggests that pyroptosis expels bacteria for uptake by bactericidal neutrophils ultimately resulting in phagocyte oxidase dependent attenuation (Miao et al 2010a).…”
Section: Role In Pathogenesismentioning
confidence: 52%
See 3 more Smart Citations
“…Similar early innate immune cell infiltrates consisting of predominantly macrophages were observed in zebrafish infected with inflammasome-activating L. monocytogenes ultimately resulting in attenuation (Fig. 7.2) (Vincent et al 2015). Previous work with Salmonella enterica subsp Typhimurium similarly engineered to robustly activate the inflammasome suggests that pyroptosis expels bacteria for uptake by bactericidal neutrophils ultimately resulting in phagocyte oxidase dependent attenuation (Miao et al 2010a).…”
Section: Role In Pathogenesismentioning
confidence: 52%
“…Both Sauer et al (2011) and Tsuchiya et al (2014) observed no increased susceptibility to L. monocytogenes in Caspase-1/11 −/− mice at 2 days post infection. Similarly, there was no increased susceptibility to L. monocytogenes in zebrafish lacking Caspase-1 (Vincent et al 2015). These studies are consistent with the tight levels of regulation observed with potential inflammasome agonists as well as the critical nature of host cell survival that has previously been reported to promote L. monocytogenes virulence.…”
Section: Role In Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical analyses for body and regenerate length were performed in R (www.r-project.org) comparing between experimental conditions using analysis of variance with Tukey method for multiple comparisons. 25 Graphs and survival analysis (logrank test) were performed using Prism 6 software (GraphPad). For all tests, p-value <0.05 was considered statistically significant.…”
Section: Viability and Wound Regrowth Assessmentmentioning
confidence: 99%